2003
DOI: 10.1046/j.1471-4159.2003.01972.x
|View full text |Cite
|
Sign up to set email alerts
|

Blood‐mediated scavenging of cerebrospinal fluid glutamate

Abstract: The maintenance of brain extracellular glutamate (Glu) at levels below its excitotoxic threshold is performed by Glu transporters present on glia and neurons as well as on brain capillary endothelial cells which remove brain Glu into blood. The feasibility of accelerating the naturally occurring brainto-blood Glu efflux was studied using paradigms based on the fate of Glu present in the cerebrospinal fluid or infused into the brain ventricles and monitored before, during, and after decreasing blood Glu levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
186
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 163 publications
(194 citation statements)
references
References 26 publications
6
186
1
1
Order By: Relevance
“…To exclude the possibility of a direct toxic effect of the OxAc treatment on glioma cells, a 3-(4,5-dimethyltiazol-2yl)-2,5-phenyl-2H-tetrazolium bromide (MTT) assay was performed on C6 cells exposed in-vitro to OxAc (3 μM–0.3 μM) for 24 h and no effect was found (data not shown). Considering our previous [4, 1921] and current results using blood Glutamate scavenging in several animal models we suggest that the therapeutic effects of OxAc on glioma growth and invasiveness in vivo are due primarily to the scavenging effect of OxAc blood Glu. In the case of glioma, our results strengthen the concept that OxAc caused in increased efflux of peritumor Glu into the blood, slowing down the ability of the tumor to create the space for its expansion.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…To exclude the possibility of a direct toxic effect of the OxAc treatment on glioma cells, a 3-(4,5-dimethyltiazol-2yl)-2,5-phenyl-2H-tetrazolium bromide (MTT) assay was performed on C6 cells exposed in-vitro to OxAc (3 μM–0.3 μM) for 24 h and no effect was found (data not shown). Considering our previous [4, 1921] and current results using blood Glutamate scavenging in several animal models we suggest that the therapeutic effects of OxAc on glioma growth and invasiveness in vivo are due primarily to the scavenging effect of OxAc blood Glu. In the case of glioma, our results strengthen the concept that OxAc caused in increased efflux of peritumor Glu into the blood, slowing down the ability of the tumor to create the space for its expansion.…”
Section: Discussionmentioning
confidence: 78%
“…We have established [19] the feasibility of accelerating this naturally occurring brain to-blood Glu efflux by decreasing blood Glu levels with intravenous oxaloacetate (OxAc) or pyruvate, the respective Glu co-substrates of the blood resident enzymes glutamate–oxaloacetate transaminase (GOT) and glutamate–pyruvate transaminase (GPT). We later demonstrated that blood Glu scavenging provides highly significant brain neuroprotection since both OxAc and pyruvate improve the neurological status of rats submitted to close head injury [2022].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to this, the capacity of the enzyme glutamate oxaloacetate transaminase (GOT) to metabolize glutamate represents a strategy to decrease glutamate levels in blood (Gottlieb et al, 2003;Teichberg et al, 2009). In fact, we observed that oxaloacetate-mediated GOT activation in an animal model of ischemia induces a neuroprotective effect, thus showing this endogenous blood enzyme as a novel neuroprotective tool against ischemic stroke (Campos et al, 2011).…”
Section: Introductionmentioning
confidence: 95%
“…As ischemic stroke is associated with an excessive release of glutamate into the brain parenchyma (Castillo et al, 1996(Castillo et al, , 1997, a decrease in blood glutamate levels provides a mechanism to increase the gradient concentration and to remove this neurotransmitter from the brain at early times, with possible therapeutic implications after an ischemic insult (Gottlieb et al, 2003;Teichberg et al, 2009).…”
Section: Introductionmentioning
confidence: 99%